1989
DOI: 10.1002/jlac.198919890227
|View full text |Cite
|
Sign up to set email alerts
|

Pilzfarbstoffe, 60 Über Leucomentine, farblose Vorstufen des Atromentins aus dem Samtfußkrempling (Paxillus atrotomentosus)

Abstract: Atromentin (1) liegt in Fruchtkörpern des Samtfußkremplings hauptsächlich in Form der farblosen Leucomentine 3–5 vor. Die Leucomentine sind Ester des Leukoatromentins mit (2Z,4S,5S)‐4,5‐Epoxy‐2‐hexensäure, deren absolute Konfiguration durch Überführung in (+)‐O‐Acetylosmundalacton (6a) bestimmt werden konnte. Dabei wurde der Mechanismus der säurekatalysierten Abspaltung der Säurereste durch 18O‐Markierung aufgeklärt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…One more species belonging to this family is Paxillus atrotomentosus , an inedible mushroom with a large cap and which frequently appears on decayed pine trees. Previously, Holzapfel et al and Besl et al reported the isolation and structural characterization of leucomentin, flavomentin, and spiromentin derivatives from this fungus collected in Europe 3,97–98. Later, some antitumor components of the cultured mycelia of Korean P. atrotomentosus 99 and ergostane‐type ecdysteroids from European P. atrotomentosus were purified 100.…”
Section: Antioxidative P‐terphenyls From Thelephoraceae and Paxillacementioning
confidence: 99%
“…One more species belonging to this family is Paxillus atrotomentosus , an inedible mushroom with a large cap and which frequently appears on decayed pine trees. Previously, Holzapfel et al and Besl et al reported the isolation and structural characterization of leucomentin, flavomentin, and spiromentin derivatives from this fungus collected in Europe 3,97–98. Later, some antitumor components of the cultured mycelia of Korean P. atrotomentosus 99 and ergostane‐type ecdysteroids from European P. atrotomentosus were purified 100.…”
Section: Antioxidative P‐terphenyls From Thelephoraceae and Paxillacementioning
confidence: 99%
“…86 All of the p-terphenyl compounds obtained from T. aurantiotincta and H. caeruleum possess two free hydroxyl groups at para position. In contrary, Japanese Thelephora terrestris elaborated p-terphenyl derivatives with two substitution groups at ortho position to each other, terrestrins A ¶G (96)(97)(98)(99)(100)(101)(102), together with three known related compounds ganbajunin B (103), 79 thelephantin F (81), and thelephantin H (83). 88 Further fractionation of the methanolic extract of T. terrestris has led to the isolation and characterization of two unusual new pregnanetype steroids, 2β,3α-dihydroxypregna-4,7,16-trien-12,20-dione (104) and 1α,2β,3α-trihydroxypregna-4,7,16-trien-12, 20-dione (105), which are named terresterones A and B (104, 105), as well as the previously known compound stizophyllin, 90 now assigned as 2β,3α,12β-trihydroxypregna-4,7,16-trien-20-one (106) (Fig.…”
Section: Antioxidative P-terphenyls From Thelephoraceae and Paxillacementioning
confidence: 99%
“…99 and ergostane-type ecdysteroids from European P. atrotomentosus were purified. 100 Meanwhile, we investigated the chemical constituents of Japanese P. atrotomentosus and a new δ-lactone, osumundalactone (120), γ-lactone (121) along with two known γ-lactone (122, 123), and six spiromentins E ¶J (124-129), together with spiromentins B and C (130-131) 97 and a novel dimeric lactone bis-osmundalactone (132) were isolated (Fig. 17).…”
Section: Antioxidative P-terphenyls From Thelephoraceae and Paxillacementioning
confidence: 99%
“…存在于自然界中 的三联苯以对位结构为主, 主要存在于蘑菇等真菌类生 物中, 间位结构的较少, 而邻位结构的目前还没有被发 现 [1] . 含有三联苯结构的化合物常常在免疫抑制活性 [2] 、 抗氧化 [3] 、神经保护活性 [4] 、细胞毒活性 [5] 以及抗血栓和 抗凝血活性 [6] 等方面具有良好的生物活性. 除此之外, 该类化合物在液晶性和电致发光性方面也表现良好 [7] , 在液晶材料方面有着广泛应用.…”
unclassified